(untitled) (Latakia University Journal - Economic and Legal Sciences Series, 2024)
This research aimed to test the effect of financial leverage on the financial performance of private commercial banks in Syria during the period 2010-2020, in addition to testing the modulating role of free cash flows on the relationship between financial leverage and financial performance. Financial performance was measured using (return on total assets), financial leverage was measured using (total debt to total assets), while free cash flows were measured using the equation (net operating profit after taxes - change in fixed assets + change in working capital)/total assets. To achieve the objective of the research, two models were relied on based on quartile data of Panel Data, and the parameters of the models were estimated using the Pooled regression model, after conducting differentiation tests (F test, Hausman test). The results showed that there is no effect of financial leverage on financial performance as measured by (rate of return on assets), and the results also showed the absence of a modulating role for free cash flows in the relationship between financial leverage and financial performance.